A STUDY OF THE INTERPRETER-RELATED FACTORS AFFECTING CONSECUTIVE INTERPRETERS’ PERFORMANCE: A THEORETICAL ACCOUNT - OTHMAN, FAWAZ MOHAMMED; AHMED, HUSSEIN ALI (Journal of Duhok University, 2023)
This study theoretically attends to the factors affecting consecutive interpreters’ performance. The information accessed in the relevant resources side by side with the researcher’s personal experience in performing the job of a consecutive interpreter have led to the identification of a set of factors that have been categorized into three main sets, namely speaker-related, interpreter-related and situation-related factors. Interpreter-related factors, that fall into 10 sub-factors, are the focus of the current study. They are related to the interpreter’s skills, knowledge, experience, and physical and mental requirements. The study is expected to aid consecutive interpreters and interpreting students to familiarize themselves with these factors, better understand their influence on their performance, and duly alleviate their impact. The conclusions drawn upon show that the interpreter-related factors do impact consecutive interpreters’ performance